Analysis of the effect of foreign investment, domestic investment and inflation on economic growth in Indonesia 2000-2022 - Salsharea Pradita; Daryono Soebagiyo (SEAN Institute, 2024)
This study analyzes the impact of Domestic Investment (PMDN), Inflation (INF), and Foreign Investment (FDI) on Indonesia's economic growth using the Error Correction Model (ECM). The results of the analysis show that PMDN has a significant effect on FDI in the short term, while INF has no significant effect. In the long run, INF has a significant impact on FDI, while PMDN does not play a significant role. The diagnosis test shows that the estimated model fits the ECM criteria, but the linearity test requires improvement. This study highlights the importance of creating a conducive environment and policy stability to attract foreign investment, and emphasizes the strategic role of FDI in economic development. The conclusions provide insights for policy makers to enhance foreign investment attraction and sustainable economic growth.